Cross-country skiing by Quebecers and where they practice: towards 'dwelling' outdoor recreational tourism. Issue 1 (2nd January 2017) - Roult, Romain; Domergue, Nadège; Auger, Denis; Adjizian, Jean-Marc
ABSTRACT: The notions of experience and ownership of practice areas have become central to the interpretation of different contemporary recreational events. The relationship to nature, the 'wild' character of certain landscapes or the authentic look of different places are now elements used by the tourism industry to promote various outdoor recreational areas. However, few studies have attempted to investigate this tourism issue through environmental psychology and the 'dwelling' concept, which logically comes down to a place of consumption, attachment, identity and social recognition. This article will present, through a quantitative methodological structure centred on a survey using questionnaires conducted among cross-country skiers ( n = 829), the type and practical arrangements that influence the perceptual relationships the skier has with his environment.